A Fitts' law evaluation and comparison for human and manipulator on touch task. Issue 3 (5th March 2022) - Guo, Xinwei
Abstract: In the near future, robots are believed to be assistants and collaborators for mankind, and robots will operate the same user interfaces with humans. Therefore, a question naturally arises whether an interface originally designed for humans is also suitable for an ordinary robot. The question is explored and discussed by considering the kinematic difference between those of humans and ordinary robots in their natural operation ways on user interface. Methodologically, Fitts' law and several motor‐related factors, such as touch accuracy, tapping efficiency, etc, are used as the evaluation principles in operations. The operation difference between humans and robot on a classic pointing task on 2D touch screen is symmetrically analysed and compared. It was found that whether the robot could finish the tasks largely related to the ratio of robot's max touch error and target width. It is believed the exploration in this work provides valuable cues for future design of user interface and intelligent algorithm in human–robot collaboration.